Abelian Theorems for the Real Weierstrass Transform over Compactly Supported Distributions - Benito J. González; Emilio Ramón Negrín; Jeetendrasingh Maan (Mathematics)
This paper explores Abelian theorems associated with the real Weierstrass transform over distributions of compact support. This study contributes to both mathematical analysis and distribution theory by offering new insights into the interaction between integral transforms and compactly supported distributions.